ENT530 : Business Model Canvas: Queenz Furniture Enterprise / Nur Hasanah Mohamad Khizam ... [et al.] - Mohamad Khizam, Nur Hasanah; Ismail, Nur Fatiha Hanum; Ab Aziz, Nur Amira Najwa; Yusof, Maizatul Atiqah; Azhar, Rabiatul Balqis (2021)
The Business Model Canvas (BMC) is a graphic description of current or new business models that strategic managers typically employ. The Canvas gives a comprehensive picture of the company as a whole, and it's especially valuable for comparing the impact of increasing investment on each of the contributing factors. The BMC provides a standard framework for evaluating traditional processes and incorporating innovation into business models. BMC's covered part includes SWOT for this business. It is important to provide SWOT because it helps form important policies. SWOT analysis may help our company to gain a better understanding of the threats and opportunities that a business may face, and it can also help to develop strong plans and policies for how you want your firm to function. At this crucial moment, the company must pay close attention to the strengths and opportunities that present themselves and capitalise on them. The components of BMC are Value Proposition, Customer Relationship, Channels, Customer Segments and others. By answering the questions of the component such as “How are these propositions to be promoted, sold and delivered? Why? Is it working?” for Channel and “How do you interact with the customer through their ‘journey’” for Customer Relationship. These components are important components to make a business run sustainably.